Marketing of development banking innovations in the financial market of Ukraine - Trusova, Natalia; Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Chkan, Iryna; Чкан, Ірина Олександрівна; Чкан, Ирина Александровна; Radchenko, Natalia; Радченко, Наталя Миколаївна; Радченко, Наталья Николаевна; Yakusheva, Inna; Якушева, Інна Євгенівна; Якушева, Инна Евгеньевна; et al. (My University, 2021)
EN: The purpose of the article is to implement a comprehensive approach to assessing the relationship between marketing of banking innovations and financial stability of banking institutions, which under the influence of digital technology determine the innovative capabilities of the banking system, activating the innovation potential of the financial market. The article presents a structural and functional model of the relationship between the priority areas of the “blue oceans” and the signs of evaluation of marketing of banking innovations. An integrated assessment of the relationship between the innovation components of the marketing complex of banking innovations and the financial stability of banking institutions of Ukraine is determined. ES: El propósito del artículo es implementar un enfoque integral para evaluar la relación entre el marketing de las innovaciones bancarias y la estabilidad financiera de las instituciones bancarias, que bajo la influencia de la tecnología digital determinan las capacidades innovadoras del sistema bancario, activando el potencial de innovación del sector financiero. mercado. El artículo presenta un modelo estructural y funcional de la relación entre las áreas prioritarias de los “océanos azules” y los signos de evaluación del marketing de innovaciones bancarias. Se determina una evaluación integrada de la relación entre los componentes de innovación del complejo de marketing de innovaciones bancarias y la estabilidad financiera de las instituciones bancarias de Ucrania.
Comercialización de innovaciones de banca de desarrollo en el mercado financiero de Ucrania
Keywords: banking innovations; banking institutions; digital technologies; financial market; innovaciones bancarias; instituciones bancarias; tecnologías digitales; mercado financiero